Estimation of erosion in a deforestation area from the amazon, Lower Acre River Basin - Bueno Francisco, Alyson (2024)
The Lower Acre River Basin is located in an area of deforestation with the implementation of pastures for beef cattle ranching in soils susceptible to erosion and equatorial climate. The existence of slaughterhouses and beef cattle in the municipality of Boca do Acre, in the state of Amazonas, is one of the problems linked to deforestation in the Brazilian Amazon. Given this scenario, an estimate of soil losses was presented with the application of the Universal Equation in a geographic information system. In the methodology, a database was elaborated with vectorized information for the extraction of the areas of the types of soils and land cover, including the spatial analysis of slopes extracted from the digital elevation model. Due to the analysis of the areas by geoprocessing occurring by vectorization, the calculations of the erosion plots were obtained through tables with the parameters adopted by the scientific references. It was found that 60% of the soil loss occurs in the area of agriculture in 11% of the territory of the watershed, being predominantly in areas of rural settlements of the state of Acre. As a result of the estimate, soil loss in the Lower Acre River Basin was 386,422 t/ha/year, with a production of 46 million tons of sediment per year.